Redesain Konsep Konsultasi Pembentukan PKPU Dalam Menindaklanjuti Putusan Mahkamah Konstitusi - Kusworo, Daffa Ladro (Jurnal Konstitusi & Demokrasi, 2025)
The research aims to identify problems in the implementation of consultation as part of the mechanism of regulation formation between KPU and DPR and the government, especially in following up the Constitutional Court's decision. The research begins by first describing the dynamics of the consultation process and its results, which are passive and tend to be formalistic after the conclusion of the RDP forum is no longer binding based on the Constitutional Court Decision 92/PUU-XIV/2016. This research uses a doctrinal method that refers to the laws and regulations related to the consultation process of the KPU together with the DPR and the government in the formation of regulations. The research aims to identify problems normatively and connect them with legal facts obtained. The research uses analytic-explanatory typology by describing the existing problems to further find the causality (cause-and-effect) of a problem. The results showed that the implementation of the RDP forum was passive and did not even pay attention to the correction of substantive errors such as in PKPU related to the requirements for former convicts to run for office. This phenomenon should be an evaluative study in the legal validity and technical procedures of the RDP forum, which turns out that there is a disharmonization of consultation provisions between the Pilkada Law and the Election Law with the MD3 Law.